Takotsubo cardiomyopathy in a 7-month-old infant with familial hemophagocytic lymphohistiocytosis: A case report - Payal Gupta; S. Sumant Patil; Usha Pillay (Wolters Kluwer Medknow Publications, 2024)
Takotsubo cardiomyopathy constitutes an acute cardiac condition that mimics acute myocardial infarction in the absence of coronary artery disease. We present a case of a 7-month-old girl, who was admitted in the pediatric intensive care unit (PICU) at a tertiary care hospital for clinical deterioration with underlying familial hemophagocytic lymphohistiocytosis. During the PICU stay, on echocardiography, the patient had severe cardiac contractility compromise with a characteristic pattern of regional wall motion abnormalities of the left ventricle. This, in combination with elevated cardiac enzymes, led to the diagnosis of takotsubo cardiomyopathy.